Formulation of Specific Personal Data Protection in Relation to Court Decisions - Amelia, Tina; Rohman, Holilur (KnE Social Sciences, 2024)
This research aims to examine and analyze the actualization of specific personal data protection in the context of court decisions. In the digital era and with the advancement of information technology, the protection of personal data has become an increasingly important and relevant issue. However, there is a need to further understand how specific personal data protection is realized and implemented in the context of court decisions. This research adopts a normative legal research method with a legislative and conceptual approach. The data used consists of primary legal materials such as legislation and court decisions related to personal data protection. Additionally, this study also refers to legal literature and expert opinions regarding personal data protection and court decisions. The results of the research indicate that the actualization of specific personal data protection in court decisions is an exception due to the principle of open court proceedings and the publication of trial outcomes. This relates to the specific personal data protection concerning criminal records. There is a need to exempt criminal records from the exceptions stated in court decisions. The importance of exempting personal data protection in the context of court decisions is also emphasized to prevent misuse in the judicial process and maintain public trust in the justice system. This research provides an important contribution to identify and analyze how specific personal data protection can be implemented in court decisions. The implications of this research are expected to provide a better understanding for relevant parties, including the judiciary, government, and the general public, regarding the importance of specific personal data protection in the context of justice. Keywords: formulation, personal data protection, court decision